Determining Factors for the Implementation of Learning Organizations in the Human Resources Bureau of the Ministry of Home Affairs - Lili Fauziah; Muh Ilham; Faria Ruhana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Changes in the strategic environment and the demands of bureaucratic reform encourage government organizations to enhance their adaptive capacity through continuous learning. In this context, the concept of a learning organization becomes particularly important, especially for human resource management units that play a strategic role in developing civil servants. This study aims to analyze the implementation of a learning organization within the Human Resources Bureau of the Ministry of Home Affairs, identify the factors influencing its implementation, and examine the efforts undertaken to optimize the application of the learning organization concept. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews with structural officials and implementing staff within the Human Resources Bureau, observations, and document review. The data were analyzed using data reduction, data presentation, and conclusion-drawing techniques, accompanied by triangulation to ensure data validity. The findings indicate that the implementation of a learning organization within the Human Resources Bureau of the Ministry of Home Affairs has been underway; however, it has not yet been fully institutionalized as an organizational culture. The five disciplines of a learning organization personal mastery, mental models, shared vision, team learning, and systems thinking have emerged in work practices, particularly in strategic activities, but remain partial and situational in nature. Supporting factors for the implementation of a learning organization include leadership commitment, policy support for the merit system, and the presence of employees with strong learning motivation. Conversely, inhibiting factors include a strong administrative work culture, uneven employee competencies, resistance to change, and weak coordination and utilization of digital systems. This study concludes that the Human Resources Bureau of the Ministry of Home Affairs is in a transitional phase toward becoming a learning organization, requiring strengthened learning leadership, a shift in mindset, and the sustained institutionalization of organizational learning.